Fuzzy Analytic Hierarchy Process Untuk Menganalisa Faktor Pemilihan Teller Terbaik - Malau, Yesni; Maulida, Ulfa (STIKOM Tunas Bangsa Pematangsiantar, 2019)
In an effort to provide motivation to improve the dedication and performance of the teller, the selection of the best teller is done periodically every year, some criteria that are performance appraisals are discipline, initiative, thorough, friendly, and speed of service, During this time the assessment of tellers by the Branch Manager does not yet have a method that can handle priority problems with many of these criteria so that the Branch Manager often has difficulty in choosing the best employee objectively.For the sake of work efficiency and effectiveness, we need an appropriate decision-making method with the aim to build and provide an alternative to a decision support system that is the Analytical Hierarchy Process (AHP) method,in the AHP method there is the concept of eigen vector for the priority ranking process of each criterion based on a pairwise comparison matrix, this will facilitate the process of selecting the best teller because the concept is simple, easy to understand,the computation is efficient and has the ability to measure performance and alternative decisions in a simple mathematical form,so that we will get the best teller who deserves to get the best teller (bonus) allowance and a better career path in the future. And application programs are made in order to facilitate the application of the use of the AHP method when implemented.